2005
DOI: 10.1142/s021827180500722x
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Superdense Star Models of Pseudo Spheroidal Space–time

Abstract: The physically viable models of compact stars like SAX (J1808.4-3658) can be obtained using Vaidya–Tikekar ansatz prescribing spheroidal geometry for their interior space–time. We discuss here the suitability of an alternative ansatz in this context. The models of superdense star are proposed using a general three parameter family of solutions of relativistic field equations obtained adopting the alternative ansatz. The setup is shown to admit physically viable models of superdense stars and strange matter sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…The effects of higher dimensions on the mass, size and density of the star is presented. The compact star solution obtained by Tikekar and Jotania [22] is recovered for D = 4. It may be pointed out here that for λ = 2 in the usual four-dimensional space-time (n = 2), the solution obtained by Tikekar and Thomas [13] is relevant.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The effects of higher dimensions on the mass, size and density of the star is presented. The compact star solution obtained by Tikekar and Jotania [22] is recovered for D = 4. It may be pointed out here that for λ = 2 in the usual four-dimensional space-time (n = 2), the solution obtained by Tikekar and Thomas [13] is relevant.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, a class of relativistic solution of compact star assuming a pseudospheroidal geometry in four dimensions was obtained by Tikekar and Jotania [22]. The motivation of the paper is to look for the effects of embedding the compact star in a higher-dimensional space-time.…”
Section: Introductionmentioning
confidence: 99%
“…X-1 and observed that the equation of state of the ReSS (realistic equation of state of strange star) approximated to linear form is derivable from models based on Vaidya-Tikekar ansatz. We have shown elsewhere [14] that the alternative ansatz suggested by Tikekar and Thomas [15] also has these features and the general threeparameter solution based on it also leads to physically plausible relativistic models of strange stars.…”
Section: Introductionmentioning
confidence: 70%
“…This approach leads to physically viable and easily tractable models of superdense stars in equilibrium. Tikekar and Jotania [87,88], Jotania and Tikekar [89] showed that the ansatz suggested by Tikekar and Thomas [90] has these features and the general three-parameter solution based on it also leads to physically plausible relativistic models of strange stars. Several aspects of physical relevance and the maximum mass of class of compact star models, based on Vaidya-Tikekar ansatz, for the both isotropic and anisotropic pressures have been investigated in [53,[91][92][93].…”
Section: Introductionmentioning
confidence: 97%